Utility of Endoscopic Examination in the Diagnosis of Acute Graft-versus-Host Disease in the Lower Gastrointestinal Tract - Kosuke Nomura; Toshiro Iizuka; Daisuke Kaji; Hisashi Yamamoto; Yasutaka Kuribayashi; Masami Tanaka; Tsukasa Furuhata; Satoshi Yamashita; Daisuke Kikuchi; Akira Matsui; Toshifumi Mitani; Yasunori Ota; et al. (Gastroenterology Research and Practice)
Background and Aims. We retrospectively investigated the incidence of acute graft-versus-host disease (GVHD) in the lower gastrointestinal (GI) tract and the diagnostic accuracy of endoscopy. Methods. Of 1231 patients who underwent allogeneic hematopoietic stem cell transplantation between January 2005 and December 2014, 186 of whom underwent colonoscopy and biopsy and had no cytomegalovirus infection. The endoscopic findings and histologic diagnosis from these 186 patients were retrospectively analyzed. Results. Based on the histopathological findings, 171 patients were diagnosed with GVHD, accounting for 13.9% of all transplant recipients. Useful endoscopic findings for the diagnosis of GVHD were atrophy of the ileocecal valve and villous atrophy in the terminal ileum and tortoise shell-like mucosae, edema, and low vascular permeability in the colon. Even when no mucosal abnormality was observed, the incidence of GVHD was 78.9% in the terminal ileum and 75.0% in the colon. Furthermore, patients with mucosal exfoliation, although infrequent, were all diagnosed with grade 3/4 GVHD. Conclusions. It is important to perform endoscopy proactively for the early diagnosis of GVHD, and biopsy should be performed even when no abnormality is observed. In addition, because patients with mucosal exfoliation are extremely likely to have grade 3/4 GVHD, early treatment should be initiated.